Pola Komunikasi Transaksional pada Edukasi Pemilahan Sampah di Masjid Salman ITB - Dhiniana Shara; Bambang Saiful Ma'arif; Asep Ahmad Siddiq (UNISBA Press, 2024)
Abstract. The issue of waste is often considered a taboo subject by society, leading to the accumulation of waste at final disposal sites. This research is deemed necessary due to the importance of continuous dissemination of preaching to the congregation to raise awareness of their surrounding environment. The objective of this research is to get to know the programs of Salman ITB Mosque, to understand the challenges, strategies, and communication patterns employed in waste separation socialization activities at Salman ITB Mosque. The research method employed is qualitative descriptive research. Data collection techniques include observation, documentation, and interviews. Data analysis techniques involve data reduction, presentation, and drawing conclusions. The research findings reveal that the preaching communication pattern established is a Transactional communication pattern applied in every waste separation socialization and education activity at Salman Mosque, ITB. The challenges in imparting knowledge about waste separation include a lack of human resources and facilities. In this study, the researcher focuses on the preaching communication pattern in waste separation socialization activities through the transactional communication model. Abstrak. Masalah sampah seringkali dianggap menjadi hal yang tabu oleh masyarakat, hal ini mengakibatkan terjadinya penumpukan sampah di tempat pemrosesan akhir (TPA). Penelitian ini dianggap perlu dilakukan karena adanya kesinambungan antara penyebarluasan dakwah kepada jamaah agar bisa mulai peka terhadap lingkungan sekitarnya. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana tantangan, strategi dan pola komunikasi apa yang digunakan dalam kegiatan sosialisasi pemilahan sampah di Masjid Salman ITB. Metode penelitian termasuk kepada penelitian kualitatif dekskriptif. Teknik pengumpulan data melalui Observasi, dokumentasi dan wawancara. Teknik analisis data melalui Reduksi data, Penyajian dan dan penarikan kesimpulan. Hasil penelitian : Pola komunikasi dakwah yang dibangun adalah pola komunikasi Transaksional yang diterapkan pada setiap kegiatan sosialisasi dan edukasi pemilahan sampah di Masjid Salman ITB. Kendala dalam memberikan pengetahuan tentang pemilahan sampah adalah kurangnya sumberdaya manusia dan sarana pra sarana. Dalam penelitian ini peneliti memfokuskan pada pola komunikasi dakwah pada kegiatan sosialisasi pemilahan sampah melalui model komunikasi transaksional.